ANALISIS KAUSALITAS ANTARA EKSPOR DAN PERTUMBUHAN EKONOMI DI ASEAN PLUS THREE - Sindy Novita Haryati; Paidi Hidayat (Ekonomi dan Keuangan, 2014)
This study aims to know whether there are a significant relationship between economic growth and export in eight ASEAN Plus three’s countries. The test are carried out using Unit Root Test, Johansen Cointegration test, Vector Auto Regretion Model (VAR), Vector Error Correction Model (VECM), and Granger Causality test for the periode 1980-2012. The result of cointegration test revealed that there are a long run relationship between economic growth and export in Indonesia, Malaysia, Thailand, Philipine, China, Japan, and South Korea, but long run relationship doesn’t occur in Singapore. Based on the result of Granger Causality test, it was found that export led growth hypothesis occur in Thailand and Philipine, while growth driven export hypothesis was occur in Indonesia, Cina, and South Korea. Bidirectional relationship was occur in Singapura, but the relationship between economic growth and export didn’t occur in Malaysia and PhilipineKey words: Economi growth, Export, Vector Auto Regretion Model (VAR), Vector Error Correction Model (VECM), and Granger Causality